Immunogenic peptides from Pap31 and SCS-? of Bartonella bacilliformis: One step closer to a rapid diagnostic tool for Carrion’s disease - Gomes C. (2021)
The study was supported by the Programa Nacional de Innovaci?n para la Competitividad y Productividad (Inn?vate Per?), under the contract 117-PNICP-PIAP-2015. J.R. had a fellowship from the program I3, of the ISCIII [grant number: CES11/012]. C.G. had a PhD fellowship of the ISCIII [FI12/00561] and was recipient of a Canon Foundation Fellowship and a Small Grant from the Royal Society for Tropical Medicine and Hygiene [grant reference 000584]. MJP had a postdoctoral fellowship from CONCYTEC/FONDECYT [grant number: CG05-2013-FONDECYT].